The relationships between technology and different teaching role attributes of instructors in Malaysia - Juhdi, Nurita; Abd Hamid, Ahmad Zohdi; Siddiq, Mohd Saeed (Canadian Center of Science and Education, 2010)
The present study seeks to examine the influence of technology on these four roles. Two hundred and ninety two lecturers teaching in Malaysian tertiary educations were involved in this study. They were using different level of technologies for teaching. Questionnaires were used to solicit their responses which were distributed using various means; online, personal visits and regular mails. The measurement items were mainly adapted from Job Diagnostic Survey developed by Hackman and Oldham. The results from the findings revealed that technology was found giving significant positive impacts on technical and managerial roles. There is no evidence to support the significant influence of technology on the other two roles. The significant findings suggest that lecturers perceive their roles in managing the course and dealing with technical aspect of the job have been enhanced with the use of technology. However, the insignificant findings imply several major issues that are worth contemplating. The main implications of the study are discussed in terms of lecturers’ teaching job design, training and performance appraisals.